Adapting the Short Digital Stress Scale (SDSS) into Turkish: validation and psychometric evaluation in adults - Geris, Ali; Esen, Erol; Soylu, Yağmur (Frontiers in Psychology, 2026)
IntroductionThis study aimed to adapt the Short Digital Stress Scale (SDSS) into Turkish and to evaluate its psychometric properties in an adult population. Digital stress has become increasingly relevant with the widespread and continuous use of digital technologies, highlighting the need for valid and reliable instruments across cultural contexts.MethodsA total of 276 adults (72.8% female, 27.2% male; M_age = 27.34, SD = 9.84) completed the SDSS together with established psychological measures, including the Bergen Social Media Addiction Scale, the Short-Form UCLA Loneliness Scale, the Liebowitz Social Anxiety Scale, and the Beck Depression Inventory-II. Confirmatory factor analysis was conducted to test the original five-factor structure of the SDSS. Convergent and concurrent validity were examined through composite reliability (CR), average variance extracted (AVE), and correlation analyses. Internal consistency was assessed using Cronbach's alpha.ResultsConfirmatory factor analysis supported the original five-factor structure—availability stress, approval anxiety, fear of missing out, connection overload, and online vigilance—with good model fit (χ2/df = 1.32, GFI = 0.99, SRMR = 0.03, RMSEA = 0.03, AGFI = 0.98, CFI = 0.99). Factor loadings ranged from 0.36 to 0.93 (p < 0.001). CR and AVE values indicated convergent validity for all factors except connection overload. Digital stress showed significant positive correlations with social media addiction, loneliness, social anxiety, and depression. Internal consistency was acceptable (α = 0.77; subdimensions = 0.67–0.85).DiscussionThe findings demonstrate that the Turkish version of the SDSS is a valid and reliable instrument for assessing digital stress among adults. The scale offers a concise and contextually appropriate tool for researchers and practitioners examining the psychological impact of digital engagement in Turkish society.